Patrício: a construção da imagem de um Santo - SANTOS, Dominique Vieira Coelho dos (2012)
Several books dedicated to the life and career of Saint Patrick seem not to take narrative problems into consideration or at least not to focus on them. The main subject in this particular field is the real or historical Patrick, in contrast to the fictional. The authors of these works try to overcome the gap between referent and representation, transcending then in order to find a hidden meaning in the past. Part of the so-called Patrician problem is related to this need of being forced to choose between real and representation. Patrick s history is analyzed differently in this research; we are more interested in understanding the representations than to transcend them. By reading some of the most important documents related to Patrick, we found three different images about him: 1) the auto-image of the Ego Patricius peccator rusticissimus, present in the Confessio and Epistola, both from the fifth century, the earliest texts to be written in Ireland we have; 2) Patrick, the apostle of all Irish people, from Muirchú s master piece Vita Sancti Patricii, written in the seventh century, associated with propaganda and political disputes between monastic houses in Ireland; 3) Patrick, the first man to visit the Purgatorium, from the Tractatus de Purgatorio Sancti Patricii Apostoli Hibernensis, written by H. of Saltrey in the twelfth century. Real and representation are two sides of the same coin. Thus, without any clear-cut distinction in this sense and not looking for a pure past, a different approach of the documents is given. Instead of thinking about the authors of these references as liars and fiction-makers, we try to comprehend the portrait of Patrick they elaborated. These representations along with those from Confessio and Epistola are crucial for the process of building the image of Patrick as a Saint.